2020
DOI: 10.3906/sag-1904-207
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of quercetin on cerebral vasospasm following experimental subarachnoid haemorrhage in rats

Abstract: The experimental protocol was approved by the Ethics Committee of Zonguldak Bülent Ecevit University. The study was conducted on thirty-eight male albino Wistar Background/aim: We examined the protective effects of the natural flavonoid, quercetin, against cerebral vasospasm in an experimental rat subarachnoid haemorrhage (SAH) model. Materials and methods: Thirty-eight albino Wistar rats were divided into five groups as follows: group 1 (G1, n=8), no experimental intervention; group 2 (G2, n=8), subarachnoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The molecule is a strong antioxidant and anti-inflammatory agent and displays potential protective properties against hypertension and ischemic heart disease in both animal models and humans [ 67 , 68 ]. Notably, quercetin and its glycosides isoquercetin (3-O-glucoside) and rutin (3-O-rutinoside) have been found to promote beneficial effects in various models of brain ischemia [ 69 , 70 , 71 , 72 , 73 , 74 ], ICH [ 75 , 76 ] and SAH [ 77 , 78 ]. The health effect of quercetin could be attributed to its antioxidant, antiapoptotic and anti-inflammatory actions, combined with a protective effect on BBB through the inhibition of metalloproteinase (MMP) activity [ 70 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Polyphenols and Stroke: Results From Preclinical Stroke Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecule is a strong antioxidant and anti-inflammatory agent and displays potential protective properties against hypertension and ischemic heart disease in both animal models and humans [ 67 , 68 ]. Notably, quercetin and its glycosides isoquercetin (3-O-glucoside) and rutin (3-O-rutinoside) have been found to promote beneficial effects in various models of brain ischemia [ 69 , 70 , 71 , 72 , 73 , 74 ], ICH [ 75 , 76 ] and SAH [ 77 , 78 ]. The health effect of quercetin could be attributed to its antioxidant, antiapoptotic and anti-inflammatory actions, combined with a protective effect on BBB through the inhibition of metalloproteinase (MMP) activity [ 70 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Polyphenols and Stroke: Results From Preclinical Stroke Mmentioning
confidence: 99%
“…Notably, quercetin and its glycosides isoquercetin (3-O-glucoside) and rutin (3-O-rutinoside) have been found to promote beneficial effects in various models of brain ischemia [ 69 , 70 , 71 , 72 , 73 , 74 ], ICH [ 75 , 76 ] and SAH [ 77 , 78 ]. The health effect of quercetin could be attributed to its antioxidant, antiapoptotic and anti-inflammatory actions, combined with a protective effect on BBB through the inhibition of metalloproteinase (MMP) activity [ 70 , 72 , 73 , 74 , 75 , 76 , 77 ]. It has been proposed that the antioxidant and antiapoptotic activity of the molecule may be mediated by the activation of Nrf2 factor [ 69 ].…”
Section: Polyphenols and Stroke: Results From Preclinical Stroke Mmentioning
confidence: 99%
“…It was found that this combination was quite effective in treating Parkinson's disease (PD) in rats [109]. The neuroprotective effects of quercetin in Wistar rats as subarachnoid hemorrhage (SAH) model animals for its role in visualizing the effects against cerebral vasospasm was reported by Gül et al [110]. The biochemical and histopathological evaluation reported revealed that quercetin has a crucial role in SAH therapy by stopping vasospasm.…”
Section: Quercetin As a Neuroprotective Agentmentioning
confidence: 90%
“…However, these relaxations were suppressed by catalase, while SOD (superoxide dismutase) had no impact, suggesting that the relaxations resulted from the direct effect of hydrogen peroxide [ 154 ]. Likewise, other than improving endothelial function [ 155 ], flavonoids may elicit favorable impacts on the vascular system, resulting in ameliorating cerebrovascular blood flow [ 156 ], potentially preventing vasospasm in SAH [ 157 ], and with therapeutic effects on ischemic stroke-induced models [ 158 ].…”
Section: Antioxidantsmentioning
confidence: 99%